Second Life : a nova identidade do jovem liminar criada no ciberespaço e os perigos da influência digital no Desafio da Baleia Azul - Ciel, Elizangela Roweder del (2023)
This paper addresses the phenomenon of cyberspace as a new space of socialization, with a focus on young people facing dangerous challenges in this environment, such as the Blue Whale Challenge. The research aims to answer the central question: does cyberspace truly constitute a new space of socialization? Additionally, it explores the dangers of the influences of this space on contemporary youth. The research's relevance stems from the ubiquity of technology in our daily lives and the shifts in social patterns promoted by social networks. The investigation seeks to analyze new modes of socialization on online platforms, which can result in harmful consequences, particularly for young individuals who often struggle to distinguish between the real and virtual worlds. The underlying hypothesis is that despite the promises of uninterrupted sociability on social networks, they may also conceal dark and threatening aspects, especially for young people who are more susceptible to external influences. The methodology employed is qualitative, involving bibliographic and descriptive research. The study aims to understand the motivations behind self-harming and even suicidal behaviors related to the increased use of social networks by young people, often influenced by cybercriminal groups, as seen in the case of the Blue Whale Challenge. In summary, this research critically examines the impact of cyberspace on youth socialization, highlighting the risks associated with virtual interaction.